Value of cardiac enzyme spectrum for the risk assessment of mortality in critically ill children: a single-centre retrospective study - Jie Wang; Xueying Chen; Junbin Huang; Cheng Shen; Huabin Wang; Lijun Gan; Chunmei Chen; Xueyun Ren (BMJ Open)
Objectives Identifying high-risk paediatric patients with a poor prognosis and providing timely and adequate treatment are critical. This study aimed to evaluate the effects of different types of cardiac enzyme spectrum within 24 hours of admission on the short-term prognosis of patients in paediatric intensive care units.Design A retrospective study.Setting A single-centre, tertiary care hospital in China, with patient data from 2010 to 2018.Participants A total of 4343 critically ill children were enrolled.Intervention None.Primary and secondary outcome measures The main outcome measure was in-hospital mortality, which was defined as death from any cause during hospitalisation. The secondary outcome was 30-day mortality, intensive care unit (ICU) length of stay (LOS) and total LOS.Results Using the local polynomial regression fitting method, an approximately linear increase in in-hospital mortality was detected for creatine kinase (CK), creatine kinase MB (CK-MB), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH). Among the different types of cardiac enzyme spectrum, LDH had the highest area under the curve value (0.729), followed by AST (0.701), CK-MB (0.613) and CK (0.557). The Kaplan‒Meier analysis showed that the patients in the high LDH group had higher 30-day mortality. The multivariate logistic regression revealed that high LDH was independently associated with in-hospital mortality (OR 2.45, 95% CI 1.84 to 3.24). After propensity score matching (PSM) and sensitivity analysis, the results remained consistent.Conclusions LDH is a reliable outcome predictor in critically ill children, including those with various comorbidities.